Jaws cysts: a correction of the accuracy of a provisional radiological diagnosis with the definitive histological diagnosis - Enahoro, Catherine Olajumoke (My University, 2018)
This study evaluated the diagnostic accuracy of panoramic and cone-beam CT (CBCT) techniques by correlating the provisional radiological diagnoses of various suspected jaw cysts with their corresponding histological diagnoses. The possible added diagnostic value of CBCT over panoramic radiography was also investigated. Thirty-five CBCT scans and panoramic radiographs of patients with suspected jaw cysts were analysed at the Wits Oral Health Centre, Johannesburg. Provisional radiological diagnoses were made by two observers using set criteria. Histological records, along with relevant clinical information of these patients were then collected from the Department of Oral Pathology. The histological diagnoses were correlated with the provisional panoramic and CBCT diagnoses using the Cohen kappa statistical method. Sensitivity and specificity tests of the radiological techniques were done. Although CBCT displayed superior overall sensitivity and specificity compared to panoramic radiography, most diagnoses correlated only moderately with the histological diagnoses (greatest with nasopalatine duct cyst k=0.82, and least with odontogenic keratocyst k=0.64; overall p value=0.00). The value of CBCT was however confirmed in its provision of additional detail useful for both diagnosis and surgical planning in most cases. Radiographic techniques alone without clinical information are insufficient in the provision of an accurate diagnosis of jaw cysts. Although CBCT shows an overall moderate agreement with the histological diagnoses of most cysts, it is invaluable in the management of jaw cysts, as it often provides important additional details not visible on panoramic radiographs. CBCT may therefore be undervalued as a highly diagnostic tool.
A research report submitted to the Faculty of Health Sciences, University of the Witwatersrand, Johannesburg, in partial fulfilment of the requirements for the degree of Master of Science, Johannesburg, 2017
Keywords: Jaw Cysts